Supportive methods for childhood acute lymphoblastic leukemia then and now: A compilation for clinical practice - Podpeskar, Alexandra; Crazzolara, Roman; Kropshofer, Gabriele; Obexer, Petra; Rabensteiner, Evelyn; Michel, Miriam; Salvador, Christina (Frontiers in Pediatrics, 2022)
Survival of childhood acute lymphoblastic leukemia has significantly improved over the past decades. In the early years of chemotherapeutic development, improvement in survival rates could be attained only by increasing the cytostatic dose, also by modulation of the frequency and combination of chemotherapeutic agents associated with severe short- and long-time side-effects and toxicity in a developing child’s organism. Years later, new treatment options have yielded promising results through targeted immune and molecular drugs, especially in relapsed and refractory leukemia, and are continuously added to conventional therapy or even replace first-line treatment. Compared to conventional strategies, these new therapies have different side-effects, requiring special supportive measures. Supportive treatment includes the prevention of serious acute and sometimes life-threatening events as well as managing therapy-related long-term side-effects and preemptive treatment of complications and is thus mandatory for successful oncological therapy. Inadequate supportive therapy is still one of the main causes of treatment failure, mortality, poor quality of life, and unsatisfactory long-term outcome in children with acute lymphoblastic leukemia. But nowadays it is a challenge to find a way through the flood of supportive recommendations and guidelines that are available in the literature. Furthermore, the development of new therapies for childhood leukemia has changed the range of supportive methods and must be observed in addition to conventional recommendations. This review aims to provide a clear and recent compilation of the most important supportive methods in the field of childhood leukemia, based on conventional regimes as well as the most promising new therapeutic approaches to date.